Effect Of Fiber Orientation And Composition Percentage To The Properties Of Particle Board From Banana Fiber - Adnan, Nor Hafizah (2018)
Shortage of wood as a raw material has forced wood-based industries to find alternative local raw materials. The use of natural source is increase in this century to protect the green environmental. Hence, the use of natural fiber is highly recommended for industrial purpose. Banana plant, an old species is developed everywhere throughout the world. All kinds of banana plants have fibers in abundance. Banana fiber has the probability to be utilized for make paper, home decorative items, home furnishing items and handicrafts. In this study, banana fibers are used as reinforcement in epoxy resins to produce new particle board. The aim of this study is to investigate the strength of new particle board from banana fiber. Physical testing of particle board from banana fiber is water absorption. The particle board from banana fiber are mechanically tested including bending (flexural) and tensile. Two Level Factorial Design was used in this experiment to gather detailed data about the interaction between parameters. A good understanding of how interactions among the various factors influence the reading of particle board specimens was obtained. The composition of 50% of banana fiber and 0 degree orientation shows the best mechanical properties on tensile strength. But the composition of 40% of banana fiber and 0 degree orientation shows the highest flexural stress and a good performance in water absorption test. At the end of this research, it reveals that tensile strength and flexural stress were significant with fiber orientation and composition percentage. But water absorption was significant only with fiber composition, not with fiber orientation. Few suggestions were proposed for the further research.